Periorbital necrotizing fasciitis: the Manchester experience - Abigail Hopkins; Jonathan K. Y. Ng; Jae Yee Ku; Adam Bull; Qistina Pilson; Anne Cook (BMC Ophthalmology)
Abstract Background To describe the presentation and management of patients with periorbital necrotizing fasciitis (PONF) through an observational retrospective case series. The clinical notes of twelve consecutive patients managed by the Oculoplastic and Orbital Service and Maxillofacial Service of the Manchester University NHS Foundation Trust between 2018 and 2023 were reviewed. Five of these patients were contactable and gave informed consent for inclusion in the study. Methods Retrospective review of patient characteristics, risk factors, clinical findings, Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score, imaging results, microbiology and histology results, patient management and mortality. Results The majority of the patients were male (n = 3) with a median (IQR) age of 63 (51–71) years. The median (IQR) number of risk factors per patient was 1 (0–1.5). All patients had periorbital swelling at presentation. Median (IQR) LRINEC score was 5 (3–8.5). Group A Streptococcus was isolated from at least one sample (wound swab, tissue sampling, blood culture) in 4 cases. Histology was consistent with PONF in the remaining case. All patients received intravenous antibiotics and had between 1 and 4 surgical debridements. The median (IQR) time from the onset of symptoms to antibiotic treatment was 24 (17–42) hours, and the time of suspected diagnosis to debridement was 4 (2.3–6) hours. The median (IQR) final best recorded visual acuity (BRVA) was 2.0 (0.23–3) logMAR. Three patients developed orbital compartment syndrome; 2 of these had a final BRVA of no perception of light (NPL). The median (IQR) time from the initial surgery to the most recent follow-up was 4 (2.5–42) months. There was no mortality. Conclusions This study showed no mortality in PONF due to early antibiotic treatment and surgical debridement. A high index of clinical suspicion for PONF using the LRINEC score and other parameters combined with a low threshold for treatment should be maintained, especially in high-risk groups. Urgent referral to specialist surgical teams to ensure prompt diagnosis and treatment is essential to optimise outcomes in the face of this destructive infection.